Pelatihan Pertolongan Pertama pada Kecelakaan (P3K) di Sekolah Menengah Pertama Kota Lubuklinggau - Aprilyadi, Nadi; Zuraidah, Zuraidah; Elviani, Yeni; Pastari, Marta (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2019)
Accident refers to an event that occurs unintentionally. For example, traffic accidents, accidents with sharp objects and so on. The word accident is taken from the root word accident. The addition of the affixes "to"... and ..."an" indicates bad luck that has happened or befalls. Technically, "accident" is not included in an event caused by someone's fault, First Aid is an act of help given to the victim with the aim of prevent the situation from getting worse before the victim gets treatment from official medical personnel.So this First Aid (PP) is not a real treatment for a disease diagnosis so that the sufferer recovers from the illness he is experiencing. First aid is usually given by people around the victim, some of whom will contact the nearest health officer. This help must be given quickly and precisely because the wrong treatment can result in bad, physical disability and even death. Schools as institutions that have been trusted by parents of course also have a responsibility in responding to their students. However, the reality is that there are often accidents in the community. school area either in the field of transportation or in other fields. This accident problem often interferes with the activities of students in teaching and learning activities so that it is appropriate for schools to make policies to deal with accidents in the school area.The main purpose of first aid in an accident is to keep the accident victim or patient alive, make the victim's condition stable, and avoid more severe disability, reduce pain, discomfort and anxiety. First aid measures in accidents that are carried out properly will reduce disability or suffering and even save the victim from death, but if first aid measures in an accident are not carried out properly, it can actually worsen the consequences of the accident and even kill the victim. It is very important to know the stages of giving first aid, especially in life-threatening situations, for example where the heart and breathing have stopped, bleeding, choking, and poisoning.